2006
DOI: 10.1183/09031936.06.00130405
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of quality of life in pulmonary hypertension and its significance

Abstract: Until recently, assessment of patients with pulmonary hypertension has mainly relied on functional and haemodynamic parameters. Health-related quality of life (HRQOL), however, has become increasingly important in defining overall health status.The present study investigated the performance and clinical relevance of the Minnesota Living with Heart Failure (MLHF) questionnaire by prospectively studying 48 patients with either pulmonary arterial hypertension (n526) or chronic thromboembolic pulmonary hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
1
9

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 32 publications
2
118
1
9
Order By: Relevance
“…On the other hand, hemodynamics had no association with either the physical or mental component scores (discriminant validity). Investigators have shown similar correlations between the physical subscore of the modified MLHF questionnaire with functional class, 6MWD, RA pressure and CI [87,107]. The MLHF score was also associated with event-free survival [107].…”
Section: Quality Of Life (Qol)mentioning
confidence: 70%
See 1 more Smart Citation
“…On the other hand, hemodynamics had no association with either the physical or mental component scores (discriminant validity). Investigators have shown similar correlations between the physical subscore of the modified MLHF questionnaire with functional class, 6MWD, RA pressure and CI [87,107]. The MLHF score was also associated with event-free survival [107].…”
Section: Quality Of Life (Qol)mentioning
confidence: 70%
“…Investigators have shown similar correlations between the physical subscore of the modified MLHF questionnaire with functional class, 6MWD, RA pressure and CI [87,107]. The MLHF score was also associated with event-free survival [107]. Chua et al have shown that improvements in 6MWD over time translate to improvements in QOL measured by the SF-36 [87].…”
Section: Quality Of Life (Qol)mentioning
confidence: 80%
“…There is growing recognition, however, that changes in physiologic measures may not always translate into a tangible benefit as perceived by the patient (7). In PAH, for example, it is known that pulmonary hemodynamics do not correlate well with how patients feel and function in their daily lives (8)(9)(10). For that reason, regulatory agencies have begun to demand that pivotal trials incorporate endpoints that are both physiologically relevant as well as patient-centered (4).…”
Section: Rationale For Using Pro Measuresmentioning
confidence: 99%
“…Given the cost and time associated with developing new instruments, it is not uncommon for investigators to modify existing measures for use in less prevalent conditions, as seen in cystic fibrosis, idiopathic pulmonary fibrosis, and sarcoidosis (20)(21)(22). In the case of PAH, cardiacand respiratory-specific instruments have frequently been used given their emphasis on the role of dyspnea and activity limitation in the disablement process (8)(9)(10)23). The validity of such instruments in PAH, however, depends in part on the extent to which those aspects of the disease that are shared in common are considered meaningful and important to patients with PAH.…”
Section: Instruments Used To Assess Hrqol In Pahmentioning
confidence: 99%
“…Yapılan çalışmalarda, çeşitli nedenlere bağlı ciddi PH olsa dahi, medikal tedavilere ek olarak direk gözetimli egzersiz eğitimi ile (solunum kas eğitimim dahil), prognostik öneme sahip olan yaşam kalitesi, VO 2 peak ve 6DYT mesafesi gibi parametrelerde kazanım-lar görülmüştür (24)(25)(26)(27). Bizim çalışmamızda da yaşam kalitesi, egzersiz kapasitesi ve VO 2 peak değerlerinde kazanımlar izlenmiştir.…”
Section: Materyal Ve Metodunclassified